Perilaku Kunjungan dan Efisiensi Penyerbukan Heterotrigona itama (Cockerell) dan Tetragonula laeviceps (Smith) (Hymenoptera: Apidae) pada Labu Siam - Qurrotu A’yunin; Aunu Rauf; Idham Sakti Harahap (Institut Pertanian Bogor, 2019)
Main insect pollinator of chayote in the neotropics is the stingless bees. In Indonesia, there is no information available on chayote pollination. Research was conducted with the objective to study the flowering phenology of chayote and the role of two specieses of stingless bees Heterotrigona itama (Cockerell) and Tetragonula laeviceps (Smith) (Hymenoptera: Apidae) on chayote pollination. Measurements included the number of staminate and pistillate flowers, volume of nectar and sugar concentration, floral handling time and visitation rate, and fruit set. Chayote plants produced more staminate flowers than pistillate flowers, with the ratio of 18:1. There was no difference in nectar volume and sugar concentration between staminate and pistillate flowers. H. itama and T. laeviceps visited both type of flowers, with the peak of daily visitation were occurred at 08:30-10:30 am local times. There were significant differences in the floral handling time and foraging rate of H. itama and T. laeviceps. Pollen load was significantly higher in H. itama (2137.50±184.49 grains) than those in T. laeviceps (1675.00±110.47 grains). H. itama seemed to deposite more pollen (14.1±4.1 grains) on stigma than T. laeviceps (9.8±3.1 grains). Flowers prevented from insect visits resulted in zero fruit set. Single flower visit by H. itama and T. laeviceps resulted in 60 and 40% fruit set, respectively. Higher percent of fruit set (80-85%) was noticed in open-pollination, suggesting that multiple visits by insect pollinators might increase the chances of successful pollination.